Antimicrobial, cytotoxic, and insulin‐releasing activities of the amphibian host‐defense peptide ocellatin‐3N and its L‐lysine‐substituted analogs. (5th December 2022) - Conlon, J. Michael; Hunter, Lauren; Attoub, Samir; Casciaro, Bruno; Mechkarska, Milena; Abdel‐Wahab, Yasser H. A.
Abstract : The host‐defense peptide ocellatin‐3N (GIFDVLKNLAKGVITSLAS.NH2 ), first isolated from the Caribbean frog Leptodactylus nesiotus, inhibited growth of clinically relevant Gram‐positive and Gram‐negative bacteria as well as a strain of the major emerging yeast pathogen Candida parapsilosis . Increasing cationicity while maintaining amphipathicity by the substitution Asp 4 →Lys increased potency against the microorganisms by between 4‐ and 16‐fold (MIC ≤3 μM) compared with the naturally occurring peptide. The substitution Ala 18 →Lys and the double substitution Asp 4 →Lys and Ala 18 →Lys had less effects on potency. The [D4K] analog also showed 2.5‐ to 4‐fold greater cytotoxic potency against non‐small‐cell lung adenocarcinoma A549 cells, breast adenocarcinoma MDA‐MB‐231 cells, and colorectal adenocarcinoma HT‐29 cells (LC50 values in the range of 12–20 μM) compared with ocellatin‐3N but was less hemolytic to mouse erythrocytes. However, the peptide showed no selectivity for tumor‐derived cells [LC50 = 20 μM for human umbilical vein endothelial cells (HUVECs)]. Ocellatin‐3N and [D4K]ocellatin‐3N stimulated the release of insulin from BRIN‐BD11 clonal β‐cells at concentrations ≥1 nM, and [A18K]ocellatin‐3N, at concentrations ≥0.1 nM. No peptide stimulated the release of lactate dehydrogenase at concentrations up to 3 μM, indicating that plasma membrane integrity had been preserved. The three peptides produced an increase in intracellular [Ca 2+ ] in BRIN‐BD11 cells when incubated at a concentration of 1 μM. In view of its high insulinotropic potency and relatively low hemolytic activity, the [A18K] ocellatin analog may represent a template for the design of agents with therapeutic potential for the treatment of patients with type 2 diabetes. Abstract : Substitution of Asp 4 by L‐Lys ([A4K]) in the frog skin peptide ocellatin‐3N led to a 4–16‐fold increase in antimicrobial activity against both Gram‐positive and Gram‐negative bacteria and a 2.5–4‐fold increase in cytotoxic potency against human tumor‐derived cells. The [A18K] analog with lower cytotoxicity was the most potent in stimulating insulin‐release from BRIN‐BD11 clonal β‐cells.